2018
DOI: 10.1177/0886260518805778
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Community, and Social Network Influences on Beliefs Concerning the Acceptability of Intimate Partner Violence in Rural Senegal

Abstract: Intimate partner violence (IPV) is a pressing international public health and human rights concern. Recent scholarship concerning causes of IPV has focused on the potentially critical influence of social learning and influence in interpersonal interaction through social norms. Using sociocentric network data from all individuals aged 16 years and above in a rural Senegalese village surveyed as part of the Niakhar Social Networks and Health Project ( n = 1,274), we estimate a series of nested linear probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…A longitudinal study on the subject would be more effective in addressing the possible causal relationship between IPV perpetration and victimization (El-Bassel, Gilbert, Wu, Go, & Hill, 2011; Testa, Livingston, & Leonard, 2003). Additional variables such as the network ties (Sandberg et al, 2021; Stephenson, Sato, Finneran, 2013), psychological traits of the respondent and the respondent’s husband (Hellmuth & McNulty, 2008; Shore, Cornelius, & Idema, 2011), and interactions between demographic and socioeconomic variables (Afifi et al, 2009; Foran & O’Leary, 2008) can be added to multivariate models to provide additional explanation to IPV victimization. This study has shown that the association between IPV perpetration and victimization cuts across 2008 and 2013, and longitudinal data will provide a clearer and deeper picture of such an association.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study on the subject would be more effective in addressing the possible causal relationship between IPV perpetration and victimization (El-Bassel, Gilbert, Wu, Go, & Hill, 2011; Testa, Livingston, & Leonard, 2003). Additional variables such as the network ties (Sandberg et al, 2021; Stephenson, Sato, Finneran, 2013), psychological traits of the respondent and the respondent’s husband (Hellmuth & McNulty, 2008; Shore, Cornelius, & Idema, 2011), and interactions between demographic and socioeconomic variables (Afifi et al, 2009; Foran & O’Leary, 2008) can be added to multivariate models to provide additional explanation to IPV victimization. This study has shown that the association between IPV perpetration and victimization cuts across 2008 and 2013, and longitudinal data will provide a clearer and deeper picture of such an association.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers found that measuring network characteristics across community settings like church and school (e.g., network diversity or the number of different social roles a person inhabits across social settings) can protect men from perpetration of sexual assault (Kaczkowski et al, 2017). More important to bystander intervention, several studies showed that attitudes like rape myth acceptance or acceptability of partner violence cluster in friend networks (Sandberg et al, 2018; Swartout, 2013). Swartout’s study found young college men whose high school male peer networks had strong rape myth acceptance and hostility toward women showed higher levels of those attitudes themselves.…”
Section: Adolescence and Social Network Of Peersmentioning
confidence: 99%
“…There was significant variation in how these items were operationalized at the individual and group levels. For example, group-level aggregates ranged from the average number of items endorsed across individuals (Jesmin, 2015, 2017; Linos et al, 2013; Nadeem & Malik, 2019; Vyas & Heise, 2016), the proportion of individuals in the group that agreed with at least one scenario (Benebo et al, 2018; Cau, 2017; Cofie, 2020; Jesmin, 2015, 2017; Yount, Roof, et al, 2018), the proportion that agreed with all statements (Mogford & Lyons, 2014), the proportion that agreed with no statements (Kadengye et al, 2019), and various cut-offs based on the proportion of individuals agreeing with at least one statement (Ahmad et al, 2019; Antai & Adaji, 2012; Sandberg et al, 2018). The remaining studies used measures of attitudes toward female autonomy, men’s controlling behavior, and equitable and inequitable gender roles.…”
Section: Resultsmentioning
confidence: 99%